Current status of renal transplantation. - Suranyi, M. G. (1990)
The success rate of renal transplantation has improved considerably during the past decade, with substantial improvements in both graft and patient survival. The quality of graft function, however, and not graft survival alone is increasingly determining the standards by which transplantation outcome is being judged. As the demand for kidney transplants continues to rise and transplants are being offered to an ever-increasing number of patients, organs are being sought from new supply pools and efforts are being made to use current resources more efficiently. Improvements in clinical management have allowed short-term complications such as infection and rejection to be better prevented or better diagnosed and treated. Fundamental advances in the understanding of the immunologic processes underlying both allograft rejection and acceptance and the introduction of new immunosuppressive agents have allowed a better use of drug therapy and have moved the goal of acquired transplant tolerance closer to attainment. With improved initial transplant success rates, the long-term transplantation outcome is becoming more important. The role of tissue matching in preventing chronic rejection is becoming more appreciated, and the long-term risks of malignancy, arteriosclerosis, and chronic rejection are being better recognized and managed.